Chk1 and 14‐3‐3 proteins inhibit atypical E2Fs to prevent a permanent cell cycle arrest. (23rd January 2018) - Yuan, Ruixue; Vos, Harmjan R; van Es, Robert M; Chen, Jing; Burgering, Boudewijn MT; Westendorp, Bart; de Bruin, Alain
Abstract: The atypical E2Fs, E2F7 and E2F8, act as potent transcriptional repressors of DNA replication genes providing them with the ability to induce a permanent S‐phase arrest and suppress tumorigenesis. Surprisingly in human cancer, transcript levels of atypical E2Fs are frequently elevated in proliferating cancer cells, suggesting that the tumor suppressor functions of atypical E2Fs might be inhibited through unknown post‐translational mechanisms. Here, we show that atypical E2Fs can be directly phosphorylated by checkpoint kinase 1 (Chk1) to prevent a permanent cell cycle arrest. We found that 14‐3‐3 protein isoforms interact with both E2Fs in a Chk1‐dependent manner. Strikingly, Chk1 phosphorylation and 14‐3‐3‐binding did not relocate or degrade atypical E2Fs, but instead, 14‐3‐3 is recruited to E2F7/8 target gene promoters to possibly interfere with transcription. We observed that high levels of 14‐3‐3 strongly correlate with upregulated transcription of atypical E2F target genes in human cancer. Thus, we reveal that Chk1 and 14‐3‐3 proteins cooperate to inactivate the transcriptional repressor functions of atypical E2Fs. This mechanism might be of particular importance to cancer cells, since they are exposed frequently to DNA‐damaging therapeutic reagents. Synopsis: Checkpoint kinase 1 (Chk1) phosphorylates atypical E2Fs (E2F7 and E2F8) and inhibits their repressor functions, by permitting the binding of 14‐3‐3 proteins. Sustaining E2F target gene expression via this pathway prevents permanent cell cycle arrest when cells in S phase are exposed to DNA damage. Transcription repressors E2F7 and E2F8 are phosphorylated by Chk1 when cells undergo DNA damage during S phase. Chk1 phosphorylation is essential for binding of 14‐3‐3 proteins to E2F7 and E2F8, which inhibits their repressor function. Chk1 inhibition leads to permanent cell cycle arrest and accumulated DNA damage lesions via sustained activity of E2F7/8. Copy number gains and enhanced expression of genes encoding 14‐3‐3 proteins correlate with elevated E2F target gene expression in multiple types of cancer. Abstract : A novel Chk1‐dependent E2F7/8‐inactivating pathway that sustains S phase gene expression upon DNA damage may also contribute to deregulated E2F target gene expression in human cancer.